Compostos fenólicos em folhas de bambu e de mirtilo desidratado, e em extrato de mirtilo aplicado em cerveja - Farias, Carla Andressa Almeida (2024)
Plant matrices are known for their bioactive potential, enhancing their antioxidant activity. These matrices can be subjected to innovative technological processes for future food and/or pharmaceutical applications. Bamboo is one such matrix, being a sustainable plant that can be fully utilized. Already used as a food additive in Asian countries due to its bioactive composition, bamboo covers approximately 35 million hectares and includes more than 125 genera and 1,670 species, necessitating a greater understanding of this plant's composition. In this context, the objective of this study was to characterize the phenolic compounds and antioxidant capacity in the leaves of 11 bamboo species. Thus, 81 phenolic compounds were identified, with 29 of them not previously reported for bamboo, and concentrations ranging from 103 to 1,291 mg/100 g. Notable groups include luteolin and apigenin, with orientin and schaftoside being the most predominant compounds within their respective groups. Additionally, the leaves exhibited considerable antioxidant capacity, indicating potential future applications in the food industry. On the other hand, another plant matrix with significant industrial potential is the blueberry, recognized as a 'superfruit' due to its bioactive constituents, although it is highly perishable and prone to post-harvest losses. To minimize these losses, the industrialization of blueberries through techniques such as dehydration and incorporation into new products has been explored. Thus, the objective was to dehydrate blueberries using a “green” technology known as Microwave Hydrodiffusion and Gravity (MHG), which simultaneously allows for the production of an aqueous extract for use in Sour beer. The results showed that MHG alone did not meet the dehydration standards required by legislation, necessitating the combination of MHG with MAC (Microwave with Air Circulation) to fully dehydrate the fruit. This method significantly reduced the dehydration time compared to conventional methods, while better preserving the phenolic constituents and antioxidant capacity of the blueberries. The pre-treatment using MHG resulted in an aqueous extract, which was used in the production of Sour beer, contributing to circular economy by reducing waste and utilizing the fruit in its entirety. The addition of the extract to the Sour beer resulted in improvements in sensory, bioactive, and physicochemical characteristics of the final product. The beer enriched with 10% extract showed a significant increase in bioactives, particularly anthocyanins, while maintaining stability for 90 days. It was also well-received sensorially and generated substantial interest in purchase.In summary, both bamboo and blueberry demonstrate significant potential in the food industry, not only offering a content of bioactive constituents but also presenting innovative solutions to reduce post-harvest losses and develop differentiated products for the market.